GEOMETRIC MODELING OF SPATIAL COVERINGS OF BUILDINGS CONSTRUCTIONS BY CHAINS OF SUCCESSIVE SUPERPOSITIONS (Academic journal Industrial Machine Building Civil Engineering, 2017)
In this article we have studied a drafting of a chain of successive superpositions of somepairs of points for modeling of a curve as a part of the frame of a curvilinear surface. It wasshown that a superposition of n points of the discrete analog of a given curve can be replacedby a chain of successive superpositions. Also we have got formulas for calculatingsuperposition coefficients of the chain, which allow determining coordinates of unknown nodalpoints of the curve without making any system of equations.